Responses of propagule germination and sexual reproduction of submerged macrophytes exposed to cadmium. (March 2019) - Cao, Yu; Liu, Hui; Sun, Junyao; Liu, Yang; Jiang, Hong Sheng; Wang, Wei; Li, Wei
Abstract: Submerged macrophytes are considered the main primary producers in shallow lakes. Recently, they have experienced a decline due to increasing environmental impacts, e.g., excessive heavy metal loads. Compared to extensive studies on vegetative growth, reports on effects of heavy metals on propagule germination and reproduction remain scarce. In this study, three experiments were conducted to investigate the effects of cadmium (Cd) on the propagule germination and sexual reproduction of submerged macrophytes. In Experiment I, six Cd concentrations were used (0, 0.05, 0.5, 1, 2.5, and 5 mg L −1 ), with seed germination found to be marginally affected by Cd treatment. In Experiment II, Cd exposure (5 d) at the six Cd concentrations was performed 15, 30, 60, 90, and 120 d prior to the designated germination date for turions/tubers. The Vallisneria spinulosa tubers did not germinate at ≥ 2.5 mg Cd L −1 when exposed to Cd 90 and 120 d prior to germination, whereas the Potamogeton crispus turions remained viable but with a low germination rate at ≥ 2.5 mg Cd L −1 . In Experiment III, with an increase from 0 to 0.5 Cd mg L −1, the fruit weight of Ottelia alismoides and V. spinulosa decreased, whereas the fruit number increased for O. alismoides but not for V. spinulosa. Furthermore, the phenology of sexual reproduction for both species advanced under Cd exposure. In summary, Cd exposure affected the germination of asexual propagules and sexual reproduction of submerged macrophytes, with seeds found to be tolerant of Cd treatment up to 5 mg L −1 . Graphical abstract: Image 1 Highlights: Three experiments for effects of Cd on propagules germination and sexual reproduction of submerged macrophytes. The seed germination were only marginally affected by Cd concentrations up to 5 mg L −1. The tuber/turion delayed the germination at higher Cd concentrations or exposed earlier to Cd. The Cd exposure affected the phenology and biomass of the sexual reproduction. Sexual reproduction and germination of asexual propagules, but not seeds were sensitive to Cd treatments.